Solve for x

x=\frac{3\left(y-4\right)}{2}

$x=23(y−4) $

Solve for y

y=\frac{2\left(x+6\right)}{3}

$y=32(x+6) $

Graph

Copy

Copied to clipboard

\frac{2}{3}x+4=y

Swap sides so that all variable terms are on the left hand side.

\frac{2}{3}x=y-4

Subtract 4 from both sides.

\frac{\frac{2}{3}x}{\frac{2}{3}}=\frac{y-4}{\frac{2}{3}}

Divide both sides of the equation by \frac{2}{3}, which is the same as multiplying both sides by the reciprocal of the fraction.

x=\frac{y-4}{\frac{2}{3}}

Dividing by \frac{2}{3} undoes the multiplication by \frac{2}{3}.

x=\frac{3y}{2}-6

Divide y-4 by \frac{2}{3} by multiplying y-4 by the reciprocal of \frac{2}{3}.

Examples

Quadratic equation

{ x } ^ { 2 } - 4 x - 5 = 0

$x_{2}−4x−5=0$

Trigonometry

4 \sin \theta \cos \theta = 2 \sin \theta

$4sinθcosθ=2sinθ$

Linear equation

y = 3x + 4

$y=3x+4$

Arithmetic

699 * 533

$699∗533$

Matrix

\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]

$[25 34 ][2−1 01 35 ]$

Simultaneous equation

\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.

${8x+2y=467x+3y=47 $

Differentiation

\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }

$dxd (x−5)(3x_{2}−2) $

Integration

\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x

$∫_{0}xe_{−x_{2}}dx$

Limits

\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}

$x→−3lim x_{2}+2x−3x_{2}−9 $